Nationalism : a very short introduction - Grosby, Steven Elliott, 1951- (Very short introductions ;, 2005)
Exploring nationality through the difficulties and conflicts that have arisen throughout history, this title discusses nations and nationalism from social, philosophical and anthropological perspectives.